Mapping of the supplementary motor area using repetitive navigated transcranial magnetic stimulation - Kern, Giulia; Kempter, Miriam; Picht, Thomas; Engelhardt, Melina (Frontiers in Neuroscience, 2023)
Background: The supplementary motor area (SMA) is important for motor and language function. Damage to the SMA may harm these functions, yet tools for a preoperative assessment of the area are still sparse. Objective: The aim of this study was to validate a mapping protocol using repetitive navigated transcranial magnetic stimulation (rnTMS) and extend this protocol for both hemispheres and lower extremities. Methods: To this purpose, the SMA of both hemispheres were mapped based on a finger tapping task for 30 healthy subjects (35.97±15.11, range 21-67 years; 14 females) using rnTMS at 20 Hz (120% resting motor threshold (RMT)) while controlling for primary motor cortex activation. Points with induced errors were marked on the corresponding MRI. Next, on the identified SMA hotspot a bimanual finger tapping task and the Nine-Hole Peg Test (NHPT) were performed. Further, the lower extremity was mapped at 20Hz (140%RMT) using a toe tapping task. Results: Mean finger tapping scores decreased significantly during stimulation (25.70taps) compared to baseline (30.48; p<0.01). Bimanual finger tapping led to a significant increase in taps during stimulation (28.43taps) compared to unimanual tapping (p<0.01). Compared to baseline, completion time for the NHPT increased significantly during stimulation (baseline: 13.6s, stimulation: 16.4s; p<0.01). No differences between hemispheres were observed. Conclusion: The current study validated and extended a rnTMS based protocol for the mapping of the SMA regarding motor function of upper and lower extremity. This protocol could be beneficial to better understand functional SMA organisation and improve preoperative planning in patients with SMA lesions.